Effectiveness of Dribbling Exercise Variations on Improving the Dribbling Ability of Basketball Players - Kunci Kunci; Wahyu Indra Bayu; Destriani Destriani (Universitas Negeri Surabaya, 2025)
Background: The purpose of this study was to analyze the effectiveness of various dribbling exercises in improving the dribbling ability of basketball players. Methods: This study used a one group pretest-post-test design. The population in this study were athletes registered at the Mustangs Academy basketball club Palembang City, totalling 30 male athletes aged 12-17 years. The test instrument used is a sports skills test in the form of a basketball dribble skill test, using the zig-zag dribble test adopted from the Johnson Basketball Test with a validity value of 0.79 and a reliability value of 0.80. The analysis was conducted using a paired sample t-test statistical test which was preceded by a normality and homogeneity test. Results: The results of this study indicate that variations in dribbling training have a significant effect on improving the dribbling ability of basketball players. Based on data analysis using the paired sample t-test at a significance level of 5% (α = 0.05), the p value is 0.023 (p < 0.05). Conclusions: Variations in dribbling exercises play a crucial role in enhancing basketball players' dribbling abilities. Implementing a mix of foundational drills, game-based scenarios, and specialized exercises like two-ball dribbling or blindfolded practices can lead to significant improvements in control, agility, and overall performance on the court. Regular practice combined with structured training programs is essential for developing effective dribbling skills that translate into better gameplay outcomes.